2014
DOI: 10.1186/s12974-014-0153-z
|View full text |Cite
|
Sign up to set email alerts
|

The immune response after hypoxia-ischemia in a mouse model of preterm brain injury

Abstract: BackgroundPreterm brain injury consists primarily of periventricular leukomalacia accompanied by elements of gray-matter injury, and these injuries are associated with cerebral palsy and cognitive impairments. Inflammation is believed to be an important contributing factor to these injuries. The aim of this study was to examine the immune response in a postnatal day (PND) 5 mouse model of preterm brain injury induced by hypoxia-ischemia (HI) that is characterized by focal white and gray-matter injury.MethodsC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 68 publications
(70 reference statements)
2
71
0
Order By: Relevance
“…PND3 and PND6 rat HI models have been used to resemble PVL in the immature brain (Jantzie et al, 2015; Zhu et al, 2017). In a PND5 mouse HI model, hypoxia-ischemia induces a pattern of diffuse white and focal gray matter injury similar to that in preterm infants with PVL (Albertsson et al, 2014). …”
Section: Animal Models Of Neonatal Hi Brain Injurymentioning
confidence: 97%
“…PND3 and PND6 rat HI models have been used to resemble PVL in the immature brain (Jantzie et al, 2015; Zhu et al, 2017). In a PND5 mouse HI model, hypoxia-ischemia induces a pattern of diffuse white and focal gray matter injury similar to that in preterm infants with PVL (Albertsson et al, 2014). …”
Section: Animal Models Of Neonatal Hi Brain Injurymentioning
confidence: 97%
“…Employing murine models to study the early stages of PVL revealed the pro-inflammatory cytokines IL-1β and TNF-α, generated during the fetal inflammatory response, mediate brain injury by increasing the permeability of the blood brain barrier (BBB) to cytotoxic proteins 90, 100, 104 . This alteration in the BBB allows an abundance of stimulated macrophages to infiltrate inflamed brain tissue 90 .…”
Section: The Role Of Chorioamnionitis and Il-17 In Cerebral Palsy Andmentioning
confidence: 99%
“…Cerebral ischemia induces an inlammatory response in the brain parenchyma and systemic circulation [34,35], resulting in the augmented secretion of proinlammatory cytokines and chemotactic molecules by the vascular endothelium in newborn infants with hypoxic-ischemic injury. Hence, cytokines are important upstream efector of brain injury after ischemia [36]. Vasoregulatory mechanisms play essential roles in brain injury and tissue reperfusion in critically ill children; endothelial dysfunction results in an imbalance between vasoconstriction and vasodilatation, which causes tissue reperfusion, cytotoxic edema, and brain injury [37].…”
Section: The Role Of Endothelial Nitric Oxide Synthase Activity In Thmentioning
confidence: 99%